Las comunidades con cactáceas del sur del Perú, II. Nueva asociación y alianza del Desierto Pacífico. - Galán de Mera, Antonio; Cáceres, César; González, Adolfo (Acta Botanica Malacitana, 2002)
The cactus communities in Southern Peru, II. A new association and alliance of the Pacific Desert. Palabras clave. Fitosociologfa, Cactaceae, Perú, Neoporteria, Haageocereus. Key words. Phytosociology, Cactaceae, Peru, Neoporteria, Haageocereus.